2020
DOI: 10.3390/biomedicines8100417
|View full text |Cite
|
Sign up to set email alerts
|

T1-Positive Mn2+-Doped Multi-Stimuli Responsive poly(L-DOPA) Nanoparticles for Photothermal and Photodynamic Combination Cancer Therapy

Abstract: In this study, we designed near-infrared (NIR)-responsive Mn2+-doped melanin-like poly(L-DOPA) nanoparticles (MNPs), which act as multifunctional nano-platforms for cancer therapy. MNPs, exhibited favorable π-π stacking, drug loading, dual stimuli (NIR and glutathione) responsive drug release, photothermal and photodynamic therapeutic activities, and T1-positive contrast for magnetic resonance imaging (MRI). First, MNPs were fabricated via KMnO4 oxidation, where the embedded Mn2+ acted as a T1-weighted contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 60 publications
(84 reference statements)
0
10
0
Order By: Relevance
“…Chemical Synthesis of PLDA NPs. PLDA NPs were synthesized through KMnO 4 oxidation of L-DOPA according to the previous method published by Kang et al 38 Briefly, L-DOPA (200 mg) was dissolved in 190 mL of deionized water under vigorous stirring. Then, 10 mL of a KMnO 4 solution (10 mM) was added to the L-DOPA aqueous solution and stirred at 50 °C for 12 h. The mixed solution was centrifuged with Amicon Ultra Centrifugal Filters (EMD Millipore, Darmstadt, Germany) at 4000 rpm for 10 min and washed three times with deionized water.…”
Section: Methodsmentioning
confidence: 99%
“…Chemical Synthesis of PLDA NPs. PLDA NPs were synthesized through KMnO 4 oxidation of L-DOPA according to the previous method published by Kang et al 38 Briefly, L-DOPA (200 mg) was dissolved in 190 mL of deionized water under vigorous stirring. Then, 10 mL of a KMnO 4 solution (10 mM) was added to the L-DOPA aqueous solution and stirred at 50 °C for 12 h. The mixed solution was centrifuged with Amicon Ultra Centrifugal Filters (EMD Millipore, Darmstadt, Germany) at 4000 rpm for 10 min and washed three times with deionized water.…”
Section: Methodsmentioning
confidence: 99%
“…10,28 It is also possible that the NIR-generated hyperthermia synergistically elevated the endocytosis of the photothermal nanoparticles. 29 Therapy based on the regulation and inhibition of keratinocyte proliferation is practical to treat psoriasis. After entering the keratinocytes, both PDA and IR820 could exhibit the photothermal effect triggered by NIR leading to cell damage.…”
Section: Biomaterials Science Papermentioning
confidence: 99%
“…In addition, Kang etal. ( 64 ) prepared dual laser-responsive multifunctional melanin-like nanoparticles (MNPs) for PDT, PTT, and chemotherapy, based on the KMnO4-oxidative polymerization of L-3,4-dihydroxyphenylalanine (L-DOPA), pheophorbide a, and Dox, and modified by FA. The results of antitumor experiments showed that after 670-nm and 808-nm laser irradiation, the MNP group showed more extensive damage and apoptosis than the control group, showing great potential for antitumor therapy.…”
Section: Classification Of Photothermal Nanomaterialsmentioning
confidence: 99%